2012
DOI: 10.5194/hessd-9-12435-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experiences in using the TRMM data to complement rain gauge data in the Ecuadorian coastal foothills

Abstract: Nowadays, new technologies are being used to expand the coverage of conventional meteorological datasets. An example of these is the TRMM data as long as one considers the bias, the type of rainfall and the current coarse spatial resolution. Although in the Guayas River Basin (Ecuadorian lowlands) the radar-based precipitation does not match the magnitude of the ground-based rainfall, at least it records somewhat the spatial pattern. The bias remains more or less steady when the temporal resolution increas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
1
0
1
Order By: Relevance
“…It is noted that the right part of the catchment shows low rainfall values at 00:00 hrs and 03:00 hrs and high rainfall values from 06:00 hrs to 18:00 hrs. This fact corroborates the concerns about possible high uncertainties that may be associated with rainfall estimation across the lower part of the Catchment (Paiva et al, 2011;Arias-Hidalgo 2013).…”
Section: Models Performance Comparisonsupporting
confidence: 84%
See 1 more Smart Citation
“…It is noted that the right part of the catchment shows low rainfall values at 00:00 hrs and 03:00 hrs and high rainfall values from 06:00 hrs to 18:00 hrs. This fact corroborates the concerns about possible high uncertainties that may be associated with rainfall estimation across the lower part of the Catchment (Paiva et al, 2011;Arias-Hidalgo 2013).…”
Section: Models Performance Comparisonsupporting
confidence: 84%
“…Recent studies have shown that the spatial resolution greatly affects the results of hydrologic and hydraulic models. Models using distributed rainfall data show better results than those using information from rain gauges (Guo et al, 2004;Smith et al, 2004;Arias-Hidalgo, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…En este contexto, el creciente interés por conocer y proteger los ecosistemas fluviales y estudiar sus cambios en el tiempo, ha estimulado en las últimas décadas el desarrollo de criterios biológicos que permitan estimar el efecto de las intervenciones humanas en ellos (Figueroa et al, 2003). Estudios de diversidad de macroinvertebrados acuáticos y de su papel en la determinación de calidad del agua en el trópico, son numerosos; Posada-García & Roldan-Pérez (2003); Chará et al (2010); Meza-S et al (2012); Arias-Hidalgo et al (2013); Giraldo et al (2014). En Ecuador, Alvarez-Mieles et al (2013) evaluaron el estado y el manejo ecológico del Humedal Abras de Mantequilla mediante el empleo de índices bióticos y su relación con factores abióticos.…”
Section: Introductionunclassified